(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
At the present time of development of biology, when not only its structure, but also its content is changing, it is necessary to identify the most significant problems and outline ways to solve them. The goal of innovative methods in teaching biology in secondary schools is a qualitative change in the student’s personality in comparison with the traditional system. This becomes possible due to the introduction into professional activity of didactic and educational programs unknown to practice, which involve the removal of the pedagogical crisis. The development of the ability to motivate actions; independently navigate the information received, the formation of creative thinking, the development of children by maximizing their natural abilities, using the latest achievements of science and practice - the main goals of innovation.